Some selected aspects of management of irrigators' associations in four provinces a Philippine case [microform] - Batoon, Jacinto R. 1940- (Photoduplication Service. University of the Philippines Library, 1979)
Thesis (M.A.)--University of the Philippines, Los Banos.